RADICAL RIGHT IDEOLOGUES IN THE AGE OF TRUMP : heralds of nihilism. - BEINER, RONALD (ROUTLEDGE, 2026)
Radical Right Ideologues in the Age of Trump offers a series of sketches of what it means to live within a new Zeitgeist where ideas of the radical right are once again attractive to young minds. The book first zeroes in on Nietzsche as a privileged philosophical source for the contemporary radical right - as a kind of prophet of the ferocious rebellion against liberal democracy evident today. It then explores this in more detail with a series of case studies of contemporary far-right ideologues and activists including Steve Bannon, Bronze Age Pervert, Alexander Dugin, Jason Jorjani, and others. This book will appeal to activists, researchers, and scholars with an interest in the contemporary radical right, fascist intellectualism, and anti-democratic ideologies.
Keywords: Trump, Donald, -- 1946-; Radicalism.; Right-wing extremists.; elektronické knihy; electronic books